Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Masa Kerja Sebagai Variabel Moderating Studi Kasus Pada Dosen Dan Karyawan Universitas Muhammadiyah Metro - Fitriani, Fitriani; Siswoyo, Slamet Tedy; Arifin, Dwi Nur (Jurnal Manajemen DIVERSIFIKASI, 2023)
This research aims to determine the influence that exists at the University of Muhammadiyah Metro, namely the lack of work motivation of lecturers or employees who have worked for a long time but do not have permanent employee status, there are several lecturers or senior employees who have lost work motivation, there is still a lack of self-awareness about how to motivate colleagues. work so as not to be late and come home early. which aims to determine the effect of work motivation on employee performance, the effect of job satisfaction on employee performance, the working period in moderating work motivation on employee performance, and the working period in moderating job satisfaction on employee performance of lecturers and employees of Muhammadiyah Metro University. Muhammadiyah Metro University employees, data collection using questionnaires, and data analysis using validity test, reliability test, normality test, homogeneity test, linearity test, multiple regression analysis, t-test, f test, r test of determination, and interaction test (moderated regression analysis). /MRA) on the IBM social sciences statistical package (SPSS). The results show that work motivation, job satisfaction, a tenure that connects motivation, and a period of service that connects satisfaction have a positive effect on employee performance, it is recommended for Muhammadiyah Metro University to increase the motivation and satisfaction of lecturers and employees of Muhammadiyah Metro University